2019
DOI: 10.1111/jgs.15919
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Interval Training on Visceral Adipose Tissue in Centrally Obese 70‐Year‐Old Individuals: A Randomized Controlled Trial

Abstract: OBJECTIVE To investigate the effects of 10 weeks of progressive vigorous‐intensity interval training as a single intervention on body composition among 70‐year‐old individuals with central obesity. DESIGN Randomized controlled trial (http://clinicaltrials.gov registration No. NCT03450655). SETTING Community‐dwelling 70‐year‐old men and women living in the Umeå municipality in Sweden. PARTICIPANTS Seventy‐seven 70‐year‐old men and women with central obesity (greater than 1 kg visceral adipose tissue [VAT] for w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
(85 reference statements)
4
10
0
Order By: Relevance
“…Given the inconsistent results, additional randomized controlled trials including older adults with hyperglycemia and dyslipidemia are required in order to establish the effectiveness of WE on cardiometabolic blood markers in older adults. In terms of feasibility, we observed a high adherence to WE (85%), which is similar to the adherence to the SE intervention [27]. This resemblance is supported by the findings from a recent systematic review [46] and may have several explanations.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Given the inconsistent results, additional randomized controlled trials including older adults with hyperglycemia and dyslipidemia are required in order to establish the effectiveness of WE on cardiometabolic blood markers in older adults. In terms of feasibility, we observed a high adherence to WE (85%), which is similar to the adherence to the SE intervention [27]. This resemblance is supported by the findings from a recent systematic review [46] and may have several explanations.…”
Section: Discussionsupporting
confidence: 84%
“…When considering the present findings in relation to previous research, a study by Wijsman and colleagues observed a somewhat larger decrease in BFP following their webbased intervention [26]. However, it should be taken into consideration that the WE group in our study had seen some positive effects already during their time as a control group [27]. Given the association between baseline values and the subsequent rate of decrease, as well as decreases being larger in the early phase of interventions [41], the observed decrease in FM and BFP may therefore be slightly underestimated.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Of interest is that MPA showed a stronger association with CVD or mortality than LPA did, which with the limitation of being an observational study may indicate that higher intensity PA could be more beneficial with respect to prevention of CVD in the older individual. In light of this, it is of interest that in two randomized controlled trials conducted in similar populations, we found that 10 weeks of high-intensity exercise had positive effects on cardiovascular risk factors in 70-year-old men and women [38][39][40].…”
Section: Discussionmentioning
confidence: 98%